Spectrum adapted expectation-conditional maximization algorithm for extending high–throughput peak separation method in XPS analysis. Issue 1 (1st January 2021) - Matsumura, Tarojiro; Nagamura, Naoka; Akaho, Shotaro; Nagata, Kenji; Ando, Yasunobu
ABSTRACT: We introduced the spectrum-adapted expectation-conditional maximization (ECM) algorithm to improve the efficiency of the peak fitting of spectral data by various fitting models. The spectrum-adapted ECM algorithm can perform the peak fitting by using the Pseudo–Voigt mixture model and Doniach–Šunjić–Gauss mixture model which are generally used for the peak fitting in the X-ray photoelectron spectroscopy. Analyses of the synthetic and experimental spectral data showed that the proposed method quickly completed the calculation and estimated well-fitted curves to spectral data. This result suggests that the spectrum adapted ECM algorithm efficiently perform the peak fitting for large number of spectral data sets. Graphical Abstract: uf0001